Primary gastrinoma of the gallbladder: a case report and review of the literature - Liu, Yao-Ge; Jiang, Shi-Tao; Zhou, Yang; Zhang, Jun-Wei; Sang, Xin-Ting; Zhang, Lei; Lu, Xin; Xu, Yi-Yao (Frontiers in Oncology, 2024)
Background Primary gallbladder gastrinoma is an exceptionally uncommon tumor and is a rare form of neuroendocrine neoplasm. Until now, no cases of primary gallbladder gastrinoma and rare cases of primary gastrinoma from the biliary system have been reported. Case presentation We report a case of a 50-year-old woman with watery diarrhea who intermittently received proton pump inhibitors (PPIs) as treatment. A serum gastrin level of 711 pg/ml was recorded after the withdrawal of PPI over 1 week. Enhanced computed tomography (CT) imaging and octreotide imaging uncovered a solitary tumor at the hepatic hilar region. During the laparoscopic surgery, it was determined that the tumor had its origin in the wall of the gallbladder neck, prompting the implementation of a laparoscopic cholecystectomy. Histological analysis revealed a primary neuroendocrine tumor from the neck of the gallbladder. The patient’s symptoms disappeared after the surgery with a follow-up of 6 months. Conclusions This case confirmed that primary gallbladder gastrinoma represents a distinct nosological entity. Immunohistochemical analysis plays a pivotal role in the diagnostic process. Given the limited understanding of primary gallbladder gastrinoma, our objective is to offer novel insights into this rare disease by delivering distinctive information and highlighting the therapeutic significance of surgical intervention.